24-Month effect of smoking cessation on cognitive function and brain structure in later life - Almeida, O.; Garrido, G.; Alfonso, Helman; Hulse, G.; Lautenschlager, N.; Hankey, G.; Flicker, L. (2011)
Background: Observational studies investigating the association between smoking, cognitive decline and dementia have produced conflicting results. We completed this trial to determine if smoking cessation decreases the progression of cognitive decline in later life. Methods: We recruited older smokers (n. =229) and never smokers (n. =98) and invited smokers to join a smoking cessation trial. The primary outcome of interest was change in Alzheimer's Disease Assessment Scale cognitive subscale (ADAS-cog) scores over 24. months. Secondary measures included the Logical Memory test and changes in gray matter density. Successful smoking cessation was defined as a minimum of 547 smoking free days during follow up. Results: The ADAS-cog scores of unsuccessful quitters (UQ) increased (i.e., became worse) 1.1 ± 0.3 and 1.2 ± 0.4 points more than the scores of never smokers (NS) (p. =0.001) and successful quitters (SQ) (p. =0.006) respectively over the 24. months of follow up. Similarly, the scores of UQ declined (i.e., became worse) relative to NS on measures of immediate (p. =0.004) and delayed recall (p. =0.029). All analyses were adjusted for age, years of education, baseline cognitive performance, alcohol use, depression scores, and the presence of chronic respiratory disease. Thirty-six NS, 18 SQ and 48 UQ completed the imaging substudy. Compared with NS, UQ showed a disproportional loss of gray matter density in the right thalamus, right and left inferior semi-lunar lobule, as well as left superior and inferior parietal lobule over 24. months. SQ showed loss of gray matter compared with NS in the right middle and inferior occipital gyri, right and left culmen, and the left superior frontal gyrus. We did not find any brain regions in which UQ had lost more gray matter than SQ over 2. years. Conclusion: These results are consistent with the hypothesis that smoking causes cognitive decline and loss of gray matter tissue in the brain over time. © 2011 Elsevier Inc.